2021
DOI: 10.3390/diagnostics11050759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Robot-Assisted Laparoscopic Partial Nephrectomy with Laparoscopic Cryoablation in the Treatment of Localised Renal Tumours: A Propensity Score-Matched Comparison of Long-Term Outcomes

Abstract: Preserving renal function and controlling oncological outcomes are pertinent when managing renal neoplasms. Cryoablation is the recommended treatment only for clinical T1a stage renal tumour. Here, we compared the outcomes of robot-assisted laparoscopic partial nephrectomy (RaPN) and laparoscopic cryoablation (LCA) in the treatment of patients with localised T1-T2 renal tumours. Overall, 86 patients who received RaPN and 78 patients underwent LCA were included in this study. The intraoperative, postoperative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…After fulfilling all the inclusion criteria, 13 studies were identified [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and another 17 studies were excluded mainly because follow-up was too short [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All of the studies had an retrospective design except the ones from Furukawa et al [ 16 ] and Beauval et al [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…After fulfilling all the inclusion criteria, 13 studies were identified [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and another 17 studies were excluded mainly because follow-up was too short [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All of the studies had an retrospective design except the ones from Furukawa et al [ 16 ] and Beauval et al [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included 13 studies ( 11 , 15 17 , 20 , 22 , 24 , 25 , 27 , 28 , 31 , 32 , 35 ) about EBL. Compared with MIPN, patients who underwent FT had significantly less EBL (SMD, −0.90; CI, −1.26 to −0.53; I 2 = 92.2%, P < 0.0001) ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Irreversible electroporation is based on a strong, short-pulsed electromagnetic field that is applied to the tissue and causes the trans-membrane potential to increase. Membrane permeability becomes irreversible when the transmembrane potential exceeds a certain threshold, resulting in cell apoptosis and necrosis [ 32 ]. This approach is not affected by the heat sink and tissue desiccation and provides greater geometric predictability for ablation and allows the sparing of the connective tissue architecture, with consequent minimal risk of damage to the adjacent healthy structures.…”
Section: Vascular and Non-vascular Approachesmentioning
confidence: 99%